Acid-Catalyzed Regioselective 1,6-Conjugate Addition of Mercaptopyridine/Hydroxypyridine to Para-Quinone Methides - Devgunde, Rupali Balaso; Rupanawar, Bapurao D.; Savekar, Amol T.; Waghmode, Suresh B. (Synthesis, 2025)
This protocol describes a trifluoroacetic acid-catalyzed regioselective 1,6-conjugate addition of mercaptopyridine and hydroxypyridine to para-quinone methides. The present reactions exhibit superior results in terms of regioselectivity, mild reaction conditions, straightforward workup (no column chromatography purification), and broad substrate scope with good functional-group compatibility. This efficient method enables the synthesis of trisubstituted methanes with pyridone and sulfide core structures.
Keywords: Mercaptopyridine; Hydroxypyridine; Regioselective; para-Quinone methides